Pengaruh Kompetensi dan Kepuasan Kerja terhadap Kinerja Pegawai pada Kantor Kecamatan Kuripan Kabupaten Barito Kuala - Rusihan Anwar; Muhammad Rudiansyah; Nurhikmah Nurhikmah (Jurnal Riset Inspirasi Manajemen dan Kewirausahaan, 2022)
This study aims to determine the effect of competence and job satisfaction partially, and which of the two independent variables has the most dominant effect on the dependent variable at the Kuripan District Office, Barito Kuala Regency.This research is a quantitative method. The data used are primary data and secondary data. The research population was 23 people. Sampling research is a population study, the technique used is total sampling. Data collection techniques were carried out by distributing questionnaires. The data analysis technique used multiple linear regression using a computer application (Statistical Package for Social Science ties) SPSS-25. The results of the study concluded that the competence variable partially had no effect on employee performance at the Kuripan District Office, Barito Kuala Regency, and job satisfaction partially had a significant effect on employee performance at the Kuripan District Office, Barito Kuala Regency. on the performance of employees at the Kuripan District Office, Barito Kuala Regency.